Pengaruh Kebijakan Moneter dan Makroprudensial terhadap Risiko Kredit di Bank Umum Syariah Periode 2018-2022 - Ambawani, Firdaina Nanda Puan; Wahyudi, Agung (ITB AAS INDONESIA Surakarta, 2024)
Abstract The impact of the financial crisis at the end of 2008 resulted in the financial sector losing its ability to mitigate risk, in turn causing increased credit risk. The aim of the study is, of course, to understand the impact of monetary policy and macroprudential on credit risks in Indonesia's non-allocation financing (NPF). The study USES the data panel that has been processed through eviews 10 and applied with multiple linear regression analysis, specifying five different types of cellular general Banks that fit the criteria as a sample of observation during the 2018-2022 period. Research shows that bi rate as a monetary policy proxy and mandatory minimum requirement (GWM) as a macroprudensian policy proxy does not significantly affect credit risk. However, those capital inequality ratios have a significant negative impact on credit risk, while those variables financing to depositite ratios have significant positive effects on credit risk. Monetary policy and macroprudencies are crucial to systemic risk, particularly credit risk in the financial sector, especially at sharia general bank.